686 Connecting with and inspiring the next generation of paediatricians in Northern Ireland. (17th August 2022) - Bell, Alison; Scott, Maura; Graham, Marcus; Sloane, Charlotte; Stewart, Gemma; Kapur, Sarah; Lewis, Julie
Abstract : Aims: Encouraging medical students and foundation trainees to consider a career in paediatrics is essential to the survival of the speciality. Service pressures and limited face to face mixing in 2021 significantly impacted on opportunities for those not currently working in paediatrics to gain an insight into the day-to-day life of a paediatrician. A group of paediatric trainees set out to engage with medical students and doctors currently in foundation training or not in a training programme and provide them with more information on a career in paediatrics Methods: A committee was formed with members of the Child Health Society (CHS) at Queen's University Belfast and Paediatric trainees from the Northern Ireland Medical and Dental Training Agency (NIMDTA) to design and deliver Northern Ireland's first virtual 'Choose Paediatrics' conference. A brainstorming session with the medical students consolidated the aims of the conference programme. The students wished for details of trainees own personal journey to paediatrics and how they balanced their family life with work. The conference was promoted to trainees using NIMDTA mailing lists for foundation trainees, the medical school at QUB emailed medical students and the CHS used social media channels to encourage their members to attend. The conference's guest speaker Prof Sir Terence Stephenson was interviewed by a medical student during which he described the development of his career in paediatrics from RCPCH president to GMC chair. Seminars provided advice on improving your CV for the application process and information on the current and future training programmes. Delegates were invited to submit abstracts on paediatric projects they had been involved with; prizewinning abstracts were chosen. There was an interactive simulated patient management presentation. Delegates voted in real time for their preferred management option during a simulated emergency situation. Results: The conference was hosted on Zoom on Wednesday 28 th April 2021 and lasted 3 hours. A total of 27 medical students and foundation trainees attended the event. Feedback revealed 72% of delegates would be very likely to recommend attending the course to a friend or colleague. Comments from delegates included 'Excellent discussion on how to apply to paediatrics and really inspiring listening to positive accounts of paediatric training' The session on Paediatric CV development was the most highly rated. The medical students valued the platform to present their abstracts. Conclusion: This small-scale project shows that with limited resources it is possible to connect with medical students and foundation trainees to promote paediatrics as a career. We hope we will continue to develop this conference into a larger scale face to face event over time and another virtual conference is planned for late Spring 2022.